Project-Based Hybrid Learning; Effectiveness, Quality of Writing A Thesis Proposal, Independence, and Learning Satisfaction - Thamrin Thamrin; Saidun Hutasuhut; Joko Suharianto; Reza Aditia (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
During the COVID-19 pandemic, it is suspected that educational institutions are facing a decline in the quality of learning because learning cannot take place face-to-face, and teaching materials and learning models applied are still conventional. The purpose of this study is to determine the effectiveness of the application of project-based hybrid learning in improving the quality of writing thesis proposals for students of the Medan State University (Unimed) Business Education Study Program and see the impact of accompaniment to learning independence and student learning satisfaction. This research method applies quasi-experimental with posttest control group design for experimental and control classes. The research population of all students currently attending the Research Methodology lecture in 2021 is 51, consisting of two classes (A & B). The sample was determined by random sampling, with class A as the experimental class of 26 people and class B as the control class of 25 people. Experimental classes are taught with project-based hybrid learning through Google meet and LMS, and control classes are taught with conventional learning through asynchronous LMS. All participants were tasked with compiling a thesis proposal after finishing the treatment. The difference in the average results of the assessment of the thesis proposals of the two classes was carried out with the Mann-Whitney test because the data were not normally distributed. The results of this study show that the application of project-based hybrid learning is effective in improving the quality of writing thesis proposals, independence, and learning satisfaction.